4x = y – 5; y = 2x + 1

(iii) 4x = y – 5; y = 2x + 1

4x = y – 5

X
 - 1
0
-2
Y
1
5
-3
(X,Y)
(-1,1)
(0,5)
(-2,-3)

Put x = - 1
4(-1) = y – 5
-4 + 5 = y
1 = y
y = 1
Put x = 0
4(0) = y – 5
0 =  y – 5
y = 5

Put x = - 2
4(-2) = y – 5
- 8 = y – 5
- 8 + 5 = y
-3 = y
y = - 3

y = 2x + 1  
X
0
1
2
Y
1
3
5
(X,Y)
(0,1)
(1,3)
(2,5)


Put x = 0
y =  2(0) + 1
y = 1
Put x = 1
y = 2(1) + 1
y = 2 + 1
y = 3
Put x = 2
y = 2(2) + 1
y = 4 + 1
y = 5




 x = - 2  and y = 3 is the solution of given simultaneous equations.